Kajian Tingkat Pemanfaatan Puskesmas Di Kecamatan Kota Blora Kabupaten Blora - Novita, Desy Ratria, Drs. Priyono, M.Si, Dra. Umrotun, M.Si (2017)
Study research utilization degree of clinics in Kota Blora Subdistrict of Blora Regency has a purpose (1) examine the extent of the influence of socioeconomic conditions towards the utilization of clinics, (2) examine how much influence it takes towards the utilization of clinics. The research method used was a survey, while in determines areas of research using the method of purposive sampling. To determine the sample using the method of stratified random sampling,the sample taken randomly based on total of strata. Total of strata made up of how long it takes the required respondents to the clinic, educational level and income of respondents.So the total of respondents obtained as many as 70. Principal data the research is data that resulted from interview by respondent. The reasearch use table frequency analysis purpose for examine score utilization clinics and correlation product moment analysis for examine influence variable the research toward utilization clinics. Output of the research stated that the utilization rate of Blora clinics with high score 10, while the low total of Medang Clinics score as 9. Variable levels of education have a negative connection towards the utilization of clinics with a value of r = -0,23. These values have the meaning level of education connection towards go down the utilization of clinics. The travel time variable has a very lowconnection with value of r = 0,13.These values have the meaning long travel time respondents have very small effect on the level of utilization clinics. While the variable income level has very low connection towards the utilization of clinics with a value of r = 0,2. These values have the meaning that the respondent's income level, has small effect towards the level of utilization of clinics.Based on the relative location of Blora clinics is located closer from central government sub-district ± 2,5 Km, where the facilities of the servicecared. So encourage visitors to make use of them. Medang Clinics located ± 6 Km from central government sub-districts.According to that location can cause of gaps between the two clinics. The Medang clinic is located farther from the central government sub-district, the gap located in the health servicefacilities. The facilities service of Blora clinics more modern than the Medang Clinics. Keyword : Level of education, Level income, and Travel time